Modeling the potential distribution of Hippophae rhamnoides in China under current and future climate scenarios using the biomod2 model - Gan, Tingjiang; He, Zhipeng; Xu, Danping; Chen, Juan; Zhang, Honghua; Wei, Xinju; Zhuo, Zhihang (Frontiers in Plant Science, 2025)
IntroductionHippophae rhamnoides, a temperate species with a transcontinental distribution spanning Eurasia, demonstrates preferential establishment in water-limited ecosystems (arid/semi-arid zones), particularly occupying high-elevation niches with skeletal soils and high solar flux. This ecologically significant plant, prized for dual ecological provisioning and economic services, shows biogeographic concentration in China’s northern desertification belts, northwestern Loess Plateau, and southwestern montane corridors. Studying the possible areas where H. rhamnoides may be found can offer a scientific foundation for the protection and sustainable management of its resources.MethodsThis study utilized the biomod2 software to assess an integrated model based on 312 distribution points and 23 environmental factors. Furthermore, a modeling analysis was conducted to examine how the geographical distribution of H. rhamnoides changes over time under the SSP245 scenario.ResultsThe findings show that the distribution of H. rhamnoides is primarily affected by three factors: annual mean temperature, temperature seasonality and mean temperature of the coldest quarter. Currently, H. rhamnoides is predominantly distributed in the provinces of Shanxi, Shaanxi, Gansu, Hebei, Yunnan, Xinjiang, Tibet, Sichuan, Qinghai, and Ningxia. The suitable habitat covers an area of 212.89×10⁴ km², which represents 22.15% of China’s total land area. Within this region, high, medium, and low suitability areas make up 23.15%, 22.66%, and 54.20% of the suitable habitat, respectively.DiscussionIn the future, the centroid of the suitable habitat for H. rhamnoides is expected to gradually shift northwest, with a trend of increasing suitability in the west and decreasing suitability in the east. This study aims to provide an in-depth exploration of the distribution of H. rhamnoides and the influence of environmental factors on it from a geographical perspective. These results are important for improving the conservation, management, cultivation, and propagation of H. rhamnoides, while also offering a scientific foundation for the research of other valuable plant species.